Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share dalam Meningkatkan Motivasi Belajar Ilmu Sosial pada Materi Interaksi Manusia dengan Lingkungan Siswa Sd Kelas Iv - Priyono Tri Febrianto; Dwi Elsa Romadhoni; Izmatul Mufidah; Siti Chomsiyatul Ma'rifah; Shofiyati Fadilah; Zainur Rohman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low motivation of students to study Social Sciences (IPS) in elementary school is still a problem that has an impact on student engagement and learning outcomes. This condition is generally related to the dominance of the use of teacher-centered learning approaches that limit students' active participation in the learning process. Therefore, this article aims to comprehensively examine the application of the Think Pair Share (TPS) type cooperative learning model as an effort to increase student learning motivation, especially in the material of human interaction with the environment in grade IV of elementary school. This study uses a descriptive qualitative approach through a literature study method by examining various relevant national and international scientific articles in the range of 2022–2026. The data was analyzed using qualitative descriptive analysis techniques by synthesizing the main findings related to learning motivation, social studies learning characteristics, and the implementation of the TPS model. The results of the study show that the TPS model has a significant role in increasing student learning motivation which is characterized by increased participation, involvement, and courage in expressing opinions. The thinking, pairing, and sharing stages encourage students' active engagement and facilitate the association of material with real-life contexts, especially in understanding human interaction with the environment. In addition, the implementation of TPS also contributes to improving students' conceptual understanding, critical thinking skills, and social skills. The study emphasizes the importance of implementing an interactive, student-centered learning model, and recommends further empirically-based research to test the effectiveness of TPS models in a more contextual way in elementary school settings.